Alzheimer’s disease: a review on the current trends of the effective diagnosis and therapeutics - Abdul Manap, Aimi Syamima; Almadodi, Reema; Sultana, Shirin; Sebastian, Maheishinii Grace; Kavani, Kenil Sureshbhai; Lyenouq, Vanessa Elle; Shankar, Aravind (Frontiers in Aging Neuroscience, 2024)
The most prevalent cause of dementia is Alzheimer's disease. Cognitive decline and accelerating memory loss characterise it. Alzheimer's disease advances sequentially, starting with preclinical stages, followed by mild cognitive and/or behavioural impairment, and ultimately leading to Alzheimer's disease dementia. In recent years, healthcare providers have been advised to make an earlier diagnosis of Alzheimer's, prior to individuals developing Alzheimer's disease dementia. Regrettably, the identification of early-stage Alzheimer's disease in clinical settings can be arduous due to the tendency of patients and healthcare providers to disregard symptoms as typical signs of aging. Therefore, accurate and prompt diagnosis of Alzheimer's disease is essential in order to facilitate the development of disease-modifying and secondary preventive therapies prior to the onset of symptoms. There has been a notable shift in the goal of the diagnosis process, transitioning from merely confirming the presence of symptomatic AD to recognising the illness in its early, asymptomatic phases. Understanding the evolution of diseasemodifying therapies and putting effective diagnostic and therapeutic management into practice requires an understanding of this concept. The outcomes of this study will enhance in-depth knowledge of the current status of Alzheimer disease's diagnosis and treatment, justifying the necessity for the quest for potential novel biomarkers that can contribute to determining the stage of the disease, particularly in its earliest stages. Interestingly, latest clinical trial status on pharmacological agents, the nonpharmacological treatments such as behaviour modification, exercise, and cognitive training as well as alternative approach on phytochemicals as neuroprotective agents have been covered in detailed.